Analisis Pengaruh Tipe Nozzle dan Tip Clerance terhadap Kinerja Propeller K-Series menggunakan Metode Computational Fluid Dynamics (CFD) - Mohamad Eko Kurniawan; Agung Purwana; Abdul Gafur (Proceedings Conference on Marine Engineering and its Application, 2023)
Many innovations have been developed in the shipbuilding industry, such as the use of waterjetand azipod propulsion systems. However, these options are considered less effective. FInally the shippingindustry has innovated by adopting ducted propeller technology. This Final Year Project aims to conductfluid flow simulation tests on the propeller with variations in nozzle sizes, namely 19A and 37 and tipclearance values of 20 mm, 30 mm, 40 mm, 50 mm, and 60 mm. The analysis is performed usingComputational Fluid Dynamics (CFD) to obtain values for thrust, torque, and efficiency. The simulationresults, the smaller tip clearance, the greater resulting thrust and torque values, namely 61874 N and 13128Nm on models with a 20 mm tip clearance. Then, the greater value of thrust or torque, the better performanceof the propeller. The largest thrust value was obtained, namely 61874 N and the largest torque, namely 13128Nm. Thus, the propeller has good performance when paired with nozzle 37. For efficiency, the better theperformance of the propeller with the recommended nozzle type and tip clearance is 37 nozzle and 20 mm tipclearance with the greatest efficiency value is at J 0.6 of 0.686.